Pengaruh Tunneling Incentive Dan Leverage Terhadap Keputusan Transfer Pricing: Pada Perusahaan Energi Yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023 - Huda Tiara; Lely Suryani (EkoPreneur, 2025)
This study aims to analyze the influence of tunneling incentive and leverage ontransfer pricing decisions in energy sector companies listed on the Indonesia StockExchange (IDX) during the 2019–2023 period. Transfer pricing refers to pricingpolicies in intercompany transactions within a business group, often used as astrategy to reduce tax burdens. Tunneling incentive reflects the controllingshareholders’ tendency to transfer company resources for personal gain, whileleverage indicates the company’s dependency on debt financing. This study employsa quantitative approach using panel data regression analysis. The tunneling incentivevariable is proxied by foreign controlling ownership exceeding 20%, leverage ismeasured by the Debt to Equity Ratio (DER), and transfer pricing is proxied by theratio of related party receivables to total receivables. The results show that bothtunneling incentive and leverage have a significant simultaneous influence ontransfer pricing decisions. Partially, both variables also have a positive andsignificant effect. These findings indicate that ownership structure and corporatefunding composition play important roles in a firm’s tendency to engage in transferpricing practices. Therefore, strengthening regulations and supervision of affiliatetransactions and ownership structures is crucial to prevent tax avoidance that harmsstate revenue. This research is expected to contribute to tax authorities, academics,and businesses by providing insights into the driving factors of transfer pricing in theIndonesian energy sector. Keywords: Tunneling Incentive, Leverage, Transfer Pricing, Energy Sector,Indonesia Stock Exchange.